Integrating Islamic Work Ethics and Organizational Culture to Enhance Employee Performance at Ternate Islamic Hospital - Arman, Arfiani; Nurlaila (Jurnal MS, 2025)
Objective: This study examines the influence of Islamic work ethics and organizational culture on employee performance at Muhammadiyah Islamic Hospital in Ternate City, emphasizing the role of value-based management in enhancing organizational outcomes. Methodology: A quantitative survey design was employed involving 70 permanent staff members. Data were analyzed using multiple regression with the Statistical Package for the Social Sciences (SPSS) to test the individual and joint effects of the independent variables on employee performance. Findings: The results indicate that Islamic work ethics and organizational culture both have positive and significant effects on employee performance, individually and collectively. These findings confirm that the integration of ethical values and cultural practices contributes to improved productivity, discipline, and work motivation. Conclusion: Islamic work ethics and organizational culture serve as complementary drivers of employee performance. Theoretically, this study enriches the literature on value-based human resource management by demonstrating the translation of religious and cultural values into effective work behaviour. Practically, the findings suggest that management should reinforce Islamic ethical principles and cultivate a strong organizational culture to achieve sustainable employee performance and organizational excellence. Keyword: Islamic work ethics; organizational culture; employee performance